GAMBARAN KLINIS DAN ELEKTROENSEFALOGRAM PASIEN STATUS EPILEPTIKUS NONKONVULSIF - Ade Wijaya,* Lubna Muhammad,* Astri Budikayanti,* Fitri Octaviana* (NEURONA, 2016)
INTRODUCTION NONCONVULSIVE STATUS EPILEPTICUS IS A CONDITION OCCURS IN 2550 PERCENT OF ADULTS WITH STATUS EPILEPTICUS THIS CONDITION OFTEN UNDERDIAGNOSED DUE TO ITS ATYPICAL FEATURES NEVERTHELESS ITS MORTALITY RATE REACHES 1865 PERCENT